Unraveling the mechanisms of intrinsic drug resistance in Mycobacterium tuberculosis - Poulton, Nicholas C.; Rock, Jeremy M. (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis (TB) is among the most difficult infections to treat, requiring several months of multidrug therapy to produce a durable cure. The reasons necessitating long treatment times are complex and multifactorial. However, the difficulty of treating TB is due in large part to the resistance of the infecting bacterium, Mycobacterium tuberculosis (Mtb), to many distinct classes of antimicrobials. This review will focus on the major gaps in our understanding of intrinsic drug resistance in Mtb and how functional and chemical-genetics can help close those gaps. A better understanding of intrinsic drug resistance will help lay the foundation for strategies to disarm and circumvent these mechanisms to develop more potent antitubercular therapies.